A HISTOLOGICAL STRUCTURE AND SPECIFIC PROTEIN OF BROWN ADIPOSE TISSUE OF MONGOLIAN LAMBS (Mongolian Journal of Agricultural Sciences, 2015)
Brown fat tissue of Mongolian lamb is divided histologically into a number of lobules with connective tissue and connective-muscular tissue septa, consists of fat cells, cytoplasm of which contains small vacuoles showing the presence of multiple lipid droplets (multilocular), and blood vessels are abundant there. However, lipid droplets in cytoplasm of brown adipose tissue /BAT/cells of 7-day old lambs enlarge and cells are generally unilocular type. Immunohistochemical analysis of this fat tissue by using specific antiserum of sheep UCP1 protein (rabbit anti-serum against UCP1)detected an antigen of UCP1 protein and approximately 350 bp length DNA fragment encoding specific protein UCP1 was found in lamb genome by PCR.Mongolian Journal of Agricultural Sciences Vol.13(2) 2014: 8-12